Immunotherapy for osteosarcoma - Kenichiro Yahiro; Yoshihiro Matsumoto (Human Vaccines & Immunotherapeutics, 2021)
Osteosarcoma (OS) is the most common malignant bone tumor and often occurs in children. Chemotherapy with methotrexate, cisplatin, doxorubicin, and ifosfamide has greatly improved the prognosis of patients with OS, and most patients have been able to preserve their limbs. However, no progress has been made in the treatment for OS in the past few decades, and the prognosis of patients with metastasis and/or local recurrence remains poor. Therefore, studies aimed at developing new treatment methods for OS are urgently required. Here, we discuss the current status of immunotherapies for OS as well as the current limitations in the field. In recent years, immunotherapy has been shown to be effective for treating several cancers, and its indication is continually increasing. Immunotherapy is also expected to be widely used for treating OS, however, the efficacy of immunotherapy for OS has not been established